Gas phase stabiliser-free production of hydrogen peroxide using supported gold–palladium catalysts - Akram, Adeeba (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Hydrogen peroxide synthesis from hydrogen and oxygen in the gas phase is postulated to be a key reaction step in the gas phase epoxidation of propene using gold–titanium silicate catalysts. During this process H(2)O(2) is consumed in a secondary step to oxidise an organic molecule so is typically not observed as a reaction product. We demonstrate that using AuPd nanoparticles, which are known to have high H(2)O(2) synthesis rates in the liquid phase, it is possible to not only oxidise organic molecules in the gas phase but to detect H(2)O(2) for the first time as a reaction product in both a fixed bed reactor and a pulsed Temporal Analysis of Products (TAP) reactor without stabilisers present in the gas feed. This observation opens up possibility of synthesising H(2)O(2) directly using a gas phase reaction.